2020
DOI: 10.1038/s41598-020-71430-y
|View full text |Cite
|
Sign up to set email alerts
|

Differences between young and older adults in physiological and subjective responses to emotion induction using films

Abstract: Emotional response in aging is typically studied using the dimensional or the discrete models of emotion. Moreover, it is typically studied using subjective or physiological variables but not using both perspectives simultaneously. Additionally, tenderness is neglected in emotion induction procedures with older adults, with the present work being the first to include the study of physiological tenderness using film clips. This study integrated two separate approaches to emotion research, comparing 68 younger a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 71 publications
3
18
0
Order By: Relevance
“…By means of network analysis, Stella, Restocchi & De Deyne (2020) detected emotions of anger, fear, and anxiety through social media in the Italian population following social distancing. When testing the effects of fear induction through film clips or virtual reality experience on participants' emotional reactivity, several studies revealed that in fear and threat conditions participants reported feeling less in control in combination with more arousal and negative valence (Fernández-Aguilar et al, 2020;Palomba et al, 2000;Thomson et al, 2019).…”
Section: Panasmentioning
confidence: 99%
“…By means of network analysis, Stella, Restocchi & De Deyne (2020) detected emotions of anger, fear, and anxiety through social media in the Italian population following social distancing. When testing the effects of fear induction through film clips or virtual reality experience on participants' emotional reactivity, several studies revealed that in fear and threat conditions participants reported feeling less in control in combination with more arousal and negative valence (Fernández-Aguilar et al, 2020;Palomba et al, 2000;Thomson et al, 2019).…”
Section: Panasmentioning
confidence: 99%
“…In addition, despite dimensional and discrete approaches to emotion are complementary, and combined could overcome the limitations attributable to each model separately (Eerola & Vuoskoski, 2011; Fernández‐Aguilar et al., 2020; Fuentes‐Sánchez et al., 2020; Harmon‐Jones et al., 2017; Stevenson & James, 2008), prior studies measuring psychophysiological correlates have generally not included both frameworks simultaneously. This theoretical caveat affects the replicability and comparability of previous results but is not exclusive to emotion elicitation through music as it extends to affective pictures and sounds.…”
Section: Introductionmentioning
confidence: 99%
“…Human reactions towards video clips have been studied using biosignals, including PPG in [ 162 , 163 , 164 ]. Lee et al [ 162 ] studied drivers’ anxiety in different situations, while Tanaka et al [ 165 ] evaluated patient anxiety before an operation by examining vascular tone taken from finger PPG.…”
Section: Potential Applications Of Ppg Signal and Impacts On Healthcarementioning
confidence: 99%
“…Perpetuini et al [ 167 ] suggested that PPG can be used in emotions recognition and estimate the state anxiety, in the field of human–machine interaction. Fernández et al [ 163 ] differentiate between subjects’ responses based on the age group. KEmoCon [ 168 ] is a dataset that used PPG along with other physiological signals to record the emotions of 32 participants in the context of social interactions.…”
Section: Potential Applications Of Ppg Signal and Impacts On Healthcarementioning
confidence: 99%